The January Effect: A South African perspective: Array - Mazviona, Batsirai; Mah, Gisele; Choga, Ireen (Acta Universitatis Danubius. Œconomica, 2021)
One of the most studied calendar anomalies is January effect and its significance in the financial realm. The objective of this article is to establish whether January effect is present on the South African equity market. Financial data for Johannesburg Stock Exchange (JSE) indices covers the period 1995-2018. Ten JSE indices namely Top 40, All Shares, Basic Materials, Industrials, Consumer Goods, Health Care, Consumer Services, Telecommunications, Financials and Technology were analysed. The January effect is modelled by Generalized Auto Regressive Conditional Heteroskedasticity Model (GARCH), exponential GARCH (EGARCH) and threshold GARCH (TGARCH) models. We estimate the GARCH models in Eviews integrated with R. Findings from the mean equation showed a positive January effect for the Top 40 and Basic materials, whilst for the variance equation, a negative January anomaly was found in the Top 40, Health care, Telecommunications, and Technology indices. The January seasonal investment style is recommended for improving returns when an investor puts money in the Basic materials sector. Diversification in the Telecommunications sector by investing in January will reduce risk for an investor. Investors can make use of other monthly investment strategies to attain positive returns on their capital. The findings reveal a shift of the traditional January effect to other months. Given the limitations in past studies, this study adds to the body of knowledge of calendar anomalies by providing a South African perspective to the discussion of January anomaly, and expanding the period of analysis to cover 1995–2018.